Stress, health & well-being : thriving in the 21st century - Harrington, Rick. (Belmont, CA : Wadsworth Cengage Learning, 2013)
Explores how stress affects health, the benefits and negative aspects of stress, and ways to manage stress to live a healthy life.
Includes bibliographical references (p. 489-521) and indexes.
Keywords: Stress (Psychology) -- 21st century; Stress (Physiology) -- 21st century; Stress management -- 21st century